Pengaruh Formula Pendidikan Keluarga Kristen dalam Menghadapi Dampak Negatif Globalisasi - Rahmat Ndruru; Milton T. Pardosi (Fakultas Keguruan dan Ilmu Pendidikan Kristen IAKN Palangka Raya, 2024)
This research explores comprehensively the influence of the Christian family education formula in facing the negative impacts of globalization with the research methodology applied, namely qualitative methods and literature studies as well as exploring the suitability of the perspective of the Christian family education formula. Humans, as social creatures, have primary needs such as clothing and food, but the need to communicate with others is also an important part of their lives. In this context, communication becomes a vital tool to enable relationships and interactions between individuals. Data was obtained through in-depth analysis from various literary sources including texts from various journals and books. The findings from this research firmly state that the right education formula applied in the family will greatly influence the determination of each family member in facing the negative impacts of globalization which have recently penetrated each of them into the joints of life, especially in the smallest cell of society, namely the family. The theological implications of these findings provide a deep understanding of the needs and challenges faced by families in facing the deep negative currents of globalization.